Diego of the dead [videorecording (DVD)] (Wownow Entertainment, 2021)
Harriba! It's The Day Of The Dead and Diego, the adorable skeleton lost his party hat, the one given to him as a gift by his dearly departed uncle Antonio! How can Diego celebrate The Day Of The Dead without his adored party hat? Diego turns for help to his best buddy Cupid. The duo teams up for the adventure of a lifetime as they travel the universe and beyond to find clues to the missing hat. Will Diego find his party hat in time for the The Day Of The Dead celebration?